2013
DOI: 10.1097/inf.0b013e31829e6798
|View full text |Cite
|
Sign up to set email alerts
|

Mannose-binding Lectin Gene Polymorphisms and Mycobacterial Lymphadenitis in Young Patients

Abstract: The present study suggests that mannose-binding lectin can protect against TB or predispose the host to the disease depending on the haplotype pair of the host. The low-expression genotype A/B and the HYB haplotype may be associated with protection against intracellular mycobacterial infections, whereas the high-expression genotype A/A may confer susceptibility to disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Further to these inconsistencies, Soborg and Selvaraj reported that low serum MBL levels could reduce tubercle bacilli infections [18,19], whilst other studies found that high of serum MBL levels [22,23] could reduce tubercle bacilli infections. Although studies have shown that Promoter -221(Y/X) mutation (YX, XX) [22] and HYB haplotype [23] could lead to decreased serum MBL [12,24] and enhanced susceptibility to TB. Liu Wei and colleagues reported that [20] the promoter -221(Y/X) mutation in the Han population was not associated with susceptibility to TB.…”
Section: Introductionmentioning
confidence: 99%
“…Further to these inconsistencies, Soborg and Selvaraj reported that low serum MBL levels could reduce tubercle bacilli infections [18,19], whilst other studies found that high of serum MBL levels [22,23] could reduce tubercle bacilli infections. Although studies have shown that Promoter -221(Y/X) mutation (YX, XX) [22] and HYB haplotype [23] could lead to decreased serum MBL [12,24] and enhanced susceptibility to TB. Liu Wei and colleagues reported that [20] the promoter -221(Y/X) mutation in the Han population was not associated with susceptibility to TB.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have indicated that mutations in the promoter and exon 1 of MBL2 may lead to the decline of MBL expression in the serum, while lower serum MBL levels can increase infections caused by tubercle bacilli [40,54], indicating that polymorphisms in MBL2 may exert a protective effect against TB. Other studies have indicated that higher serum levels of MBL can reduce tubercle bacilli infections, which are associated with wild-type MBL2 alleles [5,27,55]. These studies suggest that MBL2 variants may increase the risk for TB.…”
Section: Discussionmentioning
confidence: 77%
“…In children lectin pathway deficiencies may play a role in Haemophilus influenzae [ 20 ] but this was not found in a cohort of adults with community acquired pneumonia [ 21 ]. The effect of MBL genotype on the susceptibility to Mycobacterium tuberculosis is controversial [ 22 , 23 ]. In burn injury patients [ 16 ] and cystic fibrosis patients [ 24 ] MBL deficiency plays an important role on susceptibility to Pseudomonas aeruginosa infection and colonization.…”
Section: Discussionmentioning
confidence: 99%